Self-learned folk musician - Dukaļska, Iveta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
A folk musician is an important carrier of the folk music tradition. Most of the folk musicians are talented representatives of the musicians’ craft, highly appreciated in the 20th century by the countryside society. Music making is a must at different gatherings and family celebrations (birthday parties, weddings, seasonal festivities, etc.), and this secures a high social status for the musician within the culture environment, though this also gives rise to competition among the musicians. Along with the changes within the countryside culture environment at the turn of the 20th and 21st century, also the society’s attitude towards the folk music- making tradition has changed, on the one hand viewing it as some old-fashioned activity of elderly men (the musicians), while on the other it is viewed as an important object of study for the preservation of the tradition, its renewal and reintroduction into the culture environment of the 21st century. The present study traces the development of the notion “kaktu muzikants” (literally ‘corner musician’ – a busker; self-taught, amateur musician) in Latvia from both historical and contemporary perspective, performing the culture semiotic analysis of the symbolic and mythic meanings of corner. In the Latvian culture discourse the designation “kaktu muzikants” has the following semantic aspects: 1) in the macro space – opposition of the periphery and the centre; 2) in the micro space – a special location in the inner space (the location of the musician, while playing at the dance; the „red” corner); 3) the level of professionalism, its expressive belittlement (playing without the musical score). The present study characterises the importance of the “kaktu muzikants” in the Latvian culture in 1930’s-60’s and in the present day – in the context of the traditional instrumental music. This study also uses the field-work method in order to obtain the empiric material. During field-work the data are gathered in direct interviews, deeply or partially structured interviews, where the data are obtained from the original source in the presence of the interviewer; as the result a joint view of the culture environment of the period under study was formed, along with a view of the importance and place of a country musician in the aforementioned culture environment. In the 1930’s-40’s the folk music-making tradition is mostly a local tradition of some secluded culture environment – within the boundaries of a single family, village or parish. The first skills of music making as well as those of singing are acquired within the family, where these are inherited from the members of family belonging to the older generation. Each village and parish has its musicians. Usually within a parish a single group is formed of musicians having gained recognition by the community, with this group playing at all most important events within that community – like the weddings of the better-off families and the most important dances (e.g. the dance after the remembrance event at the local cemetery). All other musicians are peripheral musicians in relation to this main group, usually playing on their own or in duos. The situations when the music is played without a written score are self-explanatory and characteristic of folk - musicians’ technique. Lacking the knowledge of musical score, the folk - musicians mainly base on the auditory or musical memory and the song’s text, the latter taking the place of notes. In cases of purely instrumental pieces playing is based on musical hearing alone. Such a technique provides good opportunities for improvisation, and reveals the creativity of the musician, his sense of music and taste. Lack of knowledge of the musical score unites people for whom music is an important part of their lives, providing them with the experience of public performance and the sense of belonging to the group of musicians, simultaneously positioning themselves as musicians of lower status compared to those graduated from some musical education institution. The division by the level of professionalism into insiders and outsiders in relation to one or the other group of musicians was especially pronounced in 1950’s-60’s, but this division has still been retained. In any music playing situation the musician has a special place within the available space allocated to him, where this space can be either inside a house (a single room), some shed or place chosen for an open air dance as a relative space. According to the data gathered during the interviews conducted in the field, the musician most frequently is seated in the corner, that corner becoming the place of honour and the centre for the musician. The designation “kaktu muzikants” is not only current in the culture environment of the 20th century countryside, but is still retained. In 1920’s-40’s quite frequently the designation “kaktu balle” (local, less important or inferior quality dance-party) is used to indicate that the event is organised by the local community (dance at some farmstead, open air dance at some grove, etc.) as compared to more official events organised and recognised by the state institutions. With this also the designation “kaktu balles muzikants” enters currency, though this has no relation to the level of professionalism of the particular musician, instead his location – the periphery. The modern designation “kaktu muzikants” is actualised particularly in the memories of the folk musicians and their life stories of the period beginning with the 1950’s. In the vocabulary of the younger generation of musicians (meaning by that the early 21st century) “kaktu muzikants” prevails as a designation of a musician aiming at understanding of the folk music-making tradition and/or the ones who have restored a music-making tradition of some of the aforementioned periods or imitate the particular instrument technique of a single individual musician.